2019
DOI: 10.3390/ijerph16234631
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Gastronomic Image Online

Abstract: Culinary or gastronomic tourism has become one of the main exponents of cultural tourism and a key element of a destination’s image identity. Since travellers consult and produce online travel reviews (OTR) before and during a trip, this research aims to provide and implement a framework for analysing OTRs of dining establishments to measure their contribution to destination image formation in their designative (cognitive) and appraisive (affective and evaluative) aspects. To do this, a website was selected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 65 publications
1
16
0
2
Order By: Relevance
“…From the restaurant's perspective, Daries, Cristobal‐Fransi, Ferrer‐Rosell, and Marine‐Roig (2018) show that the image projected by high‐end restaurants through a mature website and relevant social media content has a positive impact on tourists' perceptions of the restaurant. Furthermore, in their research, Marine‐Roig, Ferrer‐Rosell, Daries, and Cristobal‐Fransi (2019) show that, while the gastronomic image of the destination is positive overall, the local and regional gastronomy representative of the community's socio‐cultural identity is neither the most attractive nor the best appreciated in tourists' comments. Considering a consumer perspective, Chang and Mak (2018) identified seven main attributes, namely, attractiveness, flavor profile, familiarity, cooking method and ingredients, distinctiveness, convenience and price, and health and safety that can influence positively or negatively the gastronomic image perceived by tourists.…”
Section: Introductionmentioning
confidence: 99%
“…From the restaurant's perspective, Daries, Cristobal‐Fransi, Ferrer‐Rosell, and Marine‐Roig (2018) show that the image projected by high‐end restaurants through a mature website and relevant social media content has a positive impact on tourists' perceptions of the restaurant. Furthermore, in their research, Marine‐Roig, Ferrer‐Rosell, Daries, and Cristobal‐Fransi (2019) show that, while the gastronomic image of the destination is positive overall, the local and regional gastronomy representative of the community's socio‐cultural identity is neither the most attractive nor the best appreciated in tourists' comments. Considering a consumer perspective, Chang and Mak (2018) identified seven main attributes, namely, attractiveness, flavor profile, familiarity, cooking method and ingredients, distinctiveness, convenience and price, and health and safety that can influence positively or negatively the gastronomic image perceived by tourists.…”
Section: Introductionmentioning
confidence: 99%
“…The literature review has highlighted that the number of studies that analyzed gastronomy as an element of cultural heritage and identity of tourist destinations is relatively small, despite the fact that publications increased considerably in 2019 and 2020. In addition, within these investigations, on the one hand, the use of online content generated by restaurateurs and diners as a source of data is rare, unlike other studies that have focused on gastronomic image [115][116][117]; on the other hand, most use qualitative methodologies through in depth interviews, participant observation, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this work may be representative of the situation in many tourist destinations that lack a sustainability objective in terms of gastronomy. The results of the extensive research carried out by [ 63 ] in the Canary Islands serve as an example, from which it is concluded that, according to the comments made by visitors to TripAdvisor, the two restaurants of the Hard Rock chain are the most highly valued of the islands’ gastronomic offer. So, is there a gastronomic offer?…”
Section: Discussionmentioning
confidence: 99%